Role of education in the cultural context - Kumar, Rajesh (Universal Research Reports, 2017)
In India, even a high school graduation isn't enough. An intermediate step toward a four-year college or university. A route to higher education may be found in secondary school. As a result, secondary education lacks concentration. Secondary education should have clearly defined goals and institutions should make every effort to achieve them in order to prepare students for the real world. “Culture shapes mind, it provides us with the tool kit by which we construct not only our world but our very construction of ourselves and our powers”.